Parametric bootstrap methods for testing multiplicative terms in GGE and AMMI models. Issue 3 (3rd March 2014) - Forkman, Johannes; Piepho, Hans‐Peter
Summary The genotype main effects and genotype‐by‐environment interaction effects (GGE) model and the additive main effects and multiplicative interaction (AMMI) model are two common models for analysis of genotype‐by‐environment data. These models are frequently used by agronomists, plant breeders, geneticists and statisticians for analysis of multi‐environment trials. In such trials, a set of genotypes, for example, crop cultivars, are compared across a range of environments, for example, locations. The GGE and AMMI models use singular value decomposition to partition genotype‐by‐environment interaction into an ordered sum of multiplicative terms. This article deals with the problem of testing the significance of these multiplicative terms in order to decide how many terms to retain in the final model. We propose parametric bootstrap methods for this problem. Models with fixed main effects, fixed multiplicative terms and random normally distributed errors are considered. Two methods are derived: a full and a simple parametric bootstrap method. These are compared with the alternatives of using approximate F‐tests and cross‐validation. In a simulation study based on four multi‐environment trials, both bootstrap methods performed well with regard to Type I error rate and power. The simple parametric bootstrap method is particularly easy to use, since it only involves repeated sampling of standard normally distributed values. This method is recommended for selecting the number of multiplicative terms in GGE and AMMI models. The proposed methods can also be used for testing components in principal component analysis.